Fraud Hexagon Theory” Evaluation Framework In Procurement: A Systematic Literature Review - Dewi, Sofia (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This community service initiative aims to empower residents of Takerharjo Village by introducing sustainable agricultural practices and providing health education. The goal is to improve local welfare, enhance food security, and promote community health through innovative and practical solutions. Methodology/approach: The program was conducted in Takerharjo Village, involving 50 farmers and 30 households. Sustainable agricultural tools, such as organic fertilizers, drip irrigation systems, and pest control traps, have been introduced. Health education sessions were conducted using interactive methods, including workshops and demonstrations. Surveys and interviews were conducted to assess the community's needs and to evaluate the impact of the program. Results/findings: The initiative successfully increased agricultural productivity by 25% by adopting sustainable practices. Health education has improved community awareness of hygiene and nutrition, leading to healthier lifestyles. Participants reported higher satisfaction with, and confidence in, managing their farms and health. Conclusions: The community service initiative in Takerharjo Village demonstrated that the integration of sustainable agricultural practices and health education can significantly enhance local welfare. The adoption of organic fertilizers, drip irrigation, and pest control measures has led to a measurable increase in agricultural productivity, whereas health education has fostered better hygiene and nutritional habits among residents.. Limitations: The study was limited by the short duration of the program and the small sample size, which may affect the generalizability of the results. Contribution: This study contributes to community development, sustainable agriculture, and public health. This provides a model for other rural communities to adopt similar practices, fostering local progress and well-being.